Liberation Through Radical Decentralization - Buterin, Vitalik; Weyl, E. Glen (Medium, 2018)
Wealthy societies around the world are facing a growing crisis of confidence in established authorities. Stagnating economies, mounting inequality, political corruption and the increasing monopolization of technology for the benefit of elites have provoked a populist backlash. We share and are driven by these feelings of discontent. However, we also fear that the most common responses on both the right and the left (a retreat from technology, markets and international cooperation) would destroy much of what we treasure in contemporary society while worsening the problems they seek to solve.